Buying and Selling Food Without Price Labels: The Perspective of Law No. 8 of 1999 and Islamic Law - Muhammad Julijanto; Merdikaning Anastiti (Al-Hiwalah: Journal of Sharia Economic Law, 2025)
Buying and selling food without a price tag impacts buyers, but this is regulated in Law No. 8 of 1999 and Islamic law. This study aims to determine the implementation of buying and selling without price tags in Angkringan and buying and selling food without price tags from the perspective of Law No. 8 of 1999 and Islamic Law. This research methodology uses field research and qualitative research. The data sources used are primary data sources and secondary data sources. This research is located in Angkringan, Ngringo Village, Jaten District, Karanganyar Regency. Data collection techniques are carried out through observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusions. The results of this study can be concluded that the implementation of buying and selling food at the Angkringan of Ngringo Village, Jaten District, Karanganyar Regency is carried out by taking or ordering a system, then eating and paying at the end. Five Angkringan business actors are passive regarding price information, and there is one business actor who takes the initiative to include prices. Buying and selling without a price tag violates the provisions of Article 7 of Law Number 8 of 1999. A contract, already contains elements of jahalah, ikrah, dharar, so the sale and purchase are said to be khiyar disgrace.